“Sexualized Online Bullying” Through an Equality Lens: Missed Opportunity in AB v. Bragg? - Bailey, Jane (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2014)
In AB v. Bragg, the Supreme Court of Canada ruled that fifteen-year-old AB should be allowed to use a pseudonym in seeking an order to disclose the identity of her online attacker. By framing the case as one pitting the privacy interests of a youthful victim of sexualized online bullying against principles protecting the free press and open courts, the SCC approached but ultimately skirted the central issue of equality. Without undermining the important precedent that AB achieved for youthful targets of online sexualized bullying, the author explores the case as a missed opportunity to examine the discriminatory tropes and structural inequalities that undergird the power of this kind of bullying. Viewed through an equality lens, enhanced access to pseudonymity for targets is not necessarily about privacy per se, but rather an interim measure to respond to the equality-undermining effects of sexualized online bullying—a privacy mechanism in service of equality.